Stanowisko dyplomacji brytyjskiej wobec sprawy odroczenia pierwszej sesji Komisji Przygotowawczej Konferencji Rozbrojeniowej w Genewie w 1926 r. - Szudarek, Krystian Maciej (Acta Universitatis Lodziensis. Folia Historica, 2001)
The author indicates that the perspectives of beginning of the Preparatory Commission for Disarmament Conference (PCDC) works were questionable ju s t in the moment of Commission’s appearence 12th December 1925. The United States and the Soviet Union signaled their reluctance towards sending their representatives to Geneva. The Washington administration wanted to avoid the active participation in solving complicated problems of disarmament in Europe. Moscow claimed any satisfaction from the Swiss side after the assasination of Vaclav Vorowski - Soviet representative during the Lausanne conference in 1923. In January 1926 the Franch diplomacy started its endeavoursers to adjourn the first session of PCDC. Paris was engaged in solving Soviet-Swiss controversy. There were serious anxieties in France that German delegation would try to put forward the postulate of universal and proportional disarmament. So Quai d’Orsay strove to start the negotiations after the formal Germany’s entrance into the League or Nations to make the revision of the 5th Part of Versailles Treaty impossible. The British diplomacy did not support the French proposal. Lord Cecil, the minister responsible for disarmament in the conservative Baldwin’s cabinet, considered the adjournement to be unwillingly received by the public opinion. The more serious problem for the British was the absence of the American delegation in Geneva. But the president Calvin Coolidgc’s decision to participate in PCDC works has already been known in that moment. France supported by the four other Council of the League of Nations members (Italy, Japan, Czechoslovakia, Uruguay) succeded to change the original appointed time of the First Session of PCDC. But the problems, the caused French efforts were still unsolved. Germany were still out of the League of Nations and the Soviet-Swiss impass lasted. On 18th March 1926 the Council of the League of Nations fixed the new date of the beginning of PCDC for 18th May 1926. The possibility of the further adjournement of PCDC was nor discussed again. The French Ambassador probed Foreign Office in that question in the middle of April. But the British altitude towards the next adjournement of PCDC session appeared to be negative, mainly because of the public opinion. The British diplomats also doubled the frankness of Soviet intensions and the quality Soviet Union signature under the disarmament convension draft.